Acetylcholinesterase and association of ACHE 3’ UTR SNP rs17228602 with psychiatric disorders: DOI: 10.48129/kjs.12465 - Rumman , Baseerat; Khan, Kifayatullah; Sadia, Khulah; Javeres, Mbah Ntepe Leonel; Habib, Rabia; Awan, Sliha; Nurulain , Syed Muhammad; Kornelia , Tekes (Kuwait Journal of Science, 2022)
Introduction: Psychiatric disorders are complex mental conditions that cause significant emotional distress and impairment in a person’s ability to function normally. Globally, there is an alarming rise in the prevalence of psychiatric conditions. Genetic and environmental factors are involved in the pathophysiology of these disorders, but molecular underpinning is still elusive. Cholinergic dysregulation is one of the aetiology of psychiatric condition. This study was aimed to assess the status of hydrolyzing enzyme of cholinergic neurotransmitter, acetylcholinesterase (AChE) from blood and investigate the possible association of a single nucleotide polymorphisms in 3'UTR region of ACHE (rs17228602) with predisposition to psychiatric disorder. Methods: Ninety-five confirmed psychiatric and one hundred thirty healthy individuals were recruited for the study with due consents. AChE was determined by Elman’s method. SNP was studied by polymerase chain reaction-restricted fragment length polymorphism (PCR-RFLP) and sanger sequencing on DNA samples. Results: The results showed notably reduced AChE in psychiatric cohorts with statistical significance (p≤0.05). Genotype and allelic association of the examined SNP was observed with the risk of psychiatric condition in patients. Conclusion: It is concluded that AChE activity and ACHE gene 3′-UTR variant have significant role in development of psychiatric disorders. Further studies will open new direction of investigation and therapeutic interventions for psychiatric disorders. However, further study with more study participants of homogenous composition in terms of psychiatric disorder is recommended to conclusively understand the role of ACHE gene variants in the development of psychiatric diseases.